ANTIMICROBIAL EFFECTS OF LACTOBACILLUS RHAMNOSUS AND LACTOBACILLUS BUCHNERRI FILTRATES ON THE MAIN CAUSES OF BURN INFECTIONS - GhydaaH.Aljeboury (Web of Journals Publishing, 2024)
Background: This study was done for evaluation the antimicrobial effects of Lactobacillus rhamnosus and Lactobacillus buchnerri filtrates on the main causes of burn infections. Objectives: This study was done for evaluation the antimicrobial effects of Lactobacillus rhamnosus and Lactobacillus buchnerri filtrates on the main causes of burn infections. Materials and methods: One hundred thirty-five swabs were taken from 135 burn cases from patients come to hospital in Baghdad. These swabs were cultured on primary media (mac Conkey and blood agar), then biochemical tests were done for identification of these bacteria. Lactobacillus filtrates was prepared. The antimicrobial susceptibility test for this filtrate was done by using agar well diffusion, also antibiotic susceptibility test was done for many antibiotics against bacterial isolates. Results: The current results showed that Pseudomonas aeruginosa was the most prevalent isolates from infected burns followed by E. coli. The results of susabtability test revealed that most tested microorganism were MDR toward most antibiotics, While the Lactobacillus filtrates showed a high antimicrobial affectivity against all five different bacteria. Conclusions: in conclusion, Pseudomonas aeruginosa was the widely bacteria isolated from burns, also other bacteria were isolated in significant percentages which showed high susceptibility to lactobacillus filtrates.
Keywords: Lactobacillus, Burns, Bacteria, Probiotic, Antimicrobial activity.